2018
DOI: 10.1111/dme.13607
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction: they don't talk, we don't ask

Abstract: Erectile dysfunction is an under-reported complication of diabetes mellitus affecting over half of male patients [1]. Although many men with diabetes consider that erectile dysfunction has a negative influence on their quality of life, they are reluctant to report it; and while most would like treatment, they prefer physicians to start the conversation [2][3][4]. Erectile dysfunction predicts future cardiovascular disease, and screening for erectile dysfunction is advocated in several cardiovascular risk asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The results of the present study also showed that with an increasing duration of diabetes mellitus, the prevalence of erectile dysfunction also increased. The same trend has been shown by earlier studies, which showed that as the duration of diabetes increased, so did the prevalence of erectile dysfunction in the population [ 14 - 16 ]. The underlying mechanism may be a severe vascular compromise in the form of atherosclerosis in the vascular corporal tissues, causing an inability to initiate, attain, and/or maintain penile erection [ 17 - 19 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study also showed that with an increasing duration of diabetes mellitus, the prevalence of erectile dysfunction also increased. The same trend has been shown by earlier studies, which showed that as the duration of diabetes increased, so did the prevalence of erectile dysfunction in the population [ 14 - 16 ]. The underlying mechanism may be a severe vascular compromise in the form of atherosclerosis in the vascular corporal tissues, causing an inability to initiate, attain, and/or maintain penile erection [ 17 - 19 ].…”
Section: Discussionsupporting
confidence: 82%
“…Inquires about sexual health and its related symptoms demand a lot of empathy and rapport-building with the patients so that they can express all their hidden symptoms and concerns freely with the treating physician [ 16 ]. In a culture where sexual health is considered taboo, a lot of responsibility lies on endocrinologists to educate the patients about sexual health so that can be treated for any underlying diabetes-related underlying erectile dysfunction and hypogonadism [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%